Apostrophe and Apocalypse: Notes on Theatricality in Jacques Derrida’s “Envois” - Kisiel, Michał (Theoria et Historia Scientiarum, 2017)
This article aims at uncovering and interpreting the selected theatrical tropes in Jacques Derrida’s “Envois” in relation to an interpretative path paved by Samuel Weber in Theatricality as Medium. Following Weber’s intuitions, “Envois” is read as a process of staging the postulates posed by Derrida in his previous works, including “Freud and the Scene of Writing” or “Envoi.” The logic of staging, as it is argued, relies frst and foremost on the trope of apostrophe, understood both as an act of addressing somebody and a punctuation mark. Derrida’s spectral correspondence—in which addressees, addressers, destinations, and postcards themselves engage in an ongoing play of hide and seek—employs the performative aspect of apostrophe in order to keep the deconstructive wheel in motion, in search of the genuine intimacy with the other. By means of numerous encrypted and deciphered events, actual and fctional encounters, allusions to the fort/da scene and the mirror stage, or the revisions of Matthew Paris’s illustration of Socrates and Plato, Derrida invites readers to immerse themselves in the ghostly exchange and its inherent temporal and spatial twists; the stake of this task is to follow the link joining apo-strophe with apo-calypse, with regard to the catastrophe that resides between them.